Fintech Driven DeFi Platforms Transforming Traditional Banking Structures and Regulatory Governance - Celestin, Mbonigaba; Vasuki, M; Dinesh Kumar, A; Vinayakan, K (Journal of Multidisciplinary Research Advancements, 2026)
We examine how decentralised finance platforms transform traditional banking structures under different levels of regulatory governance capacity. Using a global platform-level dataset of 43 active DeFi platforms, the study tests an integrated DeFi Bank Disruption Model linking smart contract architecture, liquidity pool mechanisms, decentralised governance protocols, and banking transformation outcomes. The findings show that smart contract architecture strengthens intermediation displacement and cost efficiency shifts by compressing execution time and reducing operational layers. Liquidity pool mechanisms reshape capital pricing and risk allocation, while decentralised governance protocols primarily accelerate innovation in service delivery. Regulatory governance capacity negatively moderates these relationships, indicating that stronger legal clarity, supervisory responsiveness, and enforcement capability dampen uncontrolled displacement and risk migration without eliminating efficiency and innovation gains. The central contribution is not the general claim that technology is institutionally shaped, but the empirical operationalisation of regulatory governance capacity as a measurable moderator of platform-level DeFi effects. The study extends financial intermediation theory by showing how decentralised platform design and institutional capacity jointly shape banking transformation across jurisdictions.